Advanced maternal age. Issue 9 (September 2019) - Walker, Kate F.; Thornton, Jim G.
Abstract: The average age of women at childbirth in industrialised nations has been increasing steadily for approximately 30 years. Women aged 35 years or over have an increased risk of gestational hypertensive disease, gestational diabetes, placenta praevia, placental abruption, perinatal death, preterm labour, fetal macrosomia and fetal growth restriction. Unsurprisingly, rates of obstetric intervention are higher among older women. Of particular concern is the increased risk of antepartum stillbirth at term in women of advanced maternal age. In all maternal age groups, the risk of stillbirth is higher among nulliparous women than among multiparous women. Women of advanced maternal age (>40 years) should be given low dose aspirin (in the presence of an additional risk factor for pre-eclampsia) and offered serial ultrasounds for fetal growth and wellbeing; given the increased risk of antepartum stillbirth, induction of labour from 39 weeks' gestation should be discussed with the woman.